Policies and Provisions for Children with Autism Spectrum Disorder in Inclusive Education Context - Acharya, Raju (Journal of Educational Research and Innovation, 2024)
This article delves into the policies and provisions designed to aid children with Autism Spectrum Disorder (ASD) within inclusive classroom environments. Drawing upon a qualitative context analysis through an examination of international declarations and Nepal's national policies, it scrutinizes the legal frameworks and educational guidelines addressing the educational requirements of children with ASD. Key international documents such as the Convention on the Rights of the Child (CRC), Education for All (EFA), and the UN Convention on the Rights of Persons with Disabilities (UN-CRPD) are analysed to discern their implications for inclusive education. Moreover, Nepal's national policies, including the National Education System Plan, National Policy and Action Plan Related to People with Disability, and the Inclusive Education Policy for Persons with Disabilities, are assessed to determine their alignment with global initiatives and effectiveness in promoting inclusive practices for children with ASD. The study emphasizes the pivotal role of these policies in shaping inclusive education environments, ensuring access to quality education, and fostering the rights of individuals with ASD to fully participate in society. Limited resources, inadequate support services, a shortage of trained teachers, and knowledge gaps among educators and stakeholders hinder the successful inclusion of students with ASD in mainstream classrooms Recommendations for policy implementation and future research directions are also deliberated to enhance support for children with ASD in inclusive classroom settings.